Attitudes of students of the Department of Musical Arts towards popular musicians in Iraq (Journal of the College of Basic Education, 2022)
Folk art in its various forms and types is the common denominator that unites the masses of the Iraqi people, and folk music is one of these arts. Since ancient times, popular music has had an important and prominent role in Iraqi society, although it is not devoid of negative aspects and disadvantages. They are many and varied in Iraqi society, as the subject requires us to study, research and analyze it from a musical point of view specialized in this field, which may reflect a positive or negative attitude of the students of the Department of Musical Arts towards popular musicians in Iraq.